PROFIL LABORATORIUM DIARE AKUT DAN DIARE KRONIS PADA ANAK DI RSUD DR. SOETOMO PERIODE JANUARI – DESEMBER 2016 - Mochammad Nasrulloh, NIM011411131044 (2017)
Diarrhea is defined as the passage of three or more loose or liquid stools per day. There are two types of diarrhea, acute and persistent. Acute diarrhea occurs less than 14 days, while persistent diarrhea occurs longer than 14 days. Diarrhea cause electrolyte change in the body. This research aims to know the laboratory results of children with acute and persistent diarrhea at RSUD Dr. Soetomo, Surabaya, from January to December 2016. There are 176 acute diarrhea patients and 13 persistent diarrhea patients during the period. This research uses analytical descriptive method with cross sectional design by observing the medical records and using SPSS to do the statistic tests, which are Mann Whitney U Test and Independent Sample T Test. The results of this research are : 54.5% of the patients are babies (<28 days-<12 months) in acute diarrhea and 53.8% in chronic diarrhea. The patients in acute diarrhea mostly are (63.1%) and the patients in persistent diarrhea are also mostly male (76.9%). Good nutrition status in acute diarrhea patients is (59.7%), while in persistent diarrhea is (46.2%). Duration of stay of acute diarrhea patient is 3 days, meanwhile in persistent diarrhea patient is 9 days. 89.8% of acute diarrhea patient and (92.3%) of persistent diarrhea patient has a good condition after being treated in hospital. (84.1%) of acute diarrhea patients and (76.9%) of persistent diarrhea patient have mild dehydration. (52.8%) of acute diarrhea patients have liquid feses and (30.1%) have lender in the feses, meanwhile in persistent diarrhea the patients with liquid conscistensy and liquid are (38.5%) and (46.2%) have mocus in their feses. (56.2%) acute diarrhea patients have normal Hb, meanwhile 53.8% persistent diarrhea patients have low Hb. (59.1%) acute diarrhea patients have normal HCT, meanwhile (53.8%) persistent diarrhea patients have low HCT. (67.6%) acute diarrhea patients and (76.9%) persistent diarrhea patients have high leukocytes count. (73.3%) acute diarrhea patients and (53.8%) persistent diarrhea patients have normal trombocytes. (58.5%) acute diarrhea patients and (69.2%) persistent diarrhea patients have normal natrium level. (67.0%) acute diarrhea patients and (46.2%) persistent diarrhea patients have normal kalium level. (65.3%) acute diarrhea patients and (53.8%) persistent diarrhea patients have high chloride level. (59.1%) acute diarrhea patients have normal calcium level and (53.8%) persistent diarrhea patients have low calcium level. There is no significant difference between age, weight, leukocytes count, thrombocytes count, natrium, kalium, chloride, and calcium level between acute and persistend diarrhea (p>0.05). A significant difference is found between the duration of hospital stay, Hb count, and HCT counts between acute and persistent diarrhea (p≤0.05).